BANKING DIGITALLY TO MICRO-BUSINESS: EXPLORING VALUE CO-CREATION STRATEGY IN NEW PRODUCT DEVELOPMENT PDF - Gunawan, Rudi; Rustiadi, Sonny (ASEAN Marketing Journal, 2021)
Manuscript type: Research Article Research Aims: To further academic knowledge around the topic of value co-creation and to provide a practical strategy for Digital Bank in Indonesia on conducting better co-creation activities. Design/methodology/approach: This research relies on a qualitative method for collecting the primary data through in-depth interviews. Research Findings: Indonesian Bank called Jenius currently practice community-based value co-creation, and it is recommended for the Banks in general to also explore other forms of co-creation initiatives, namely customization, reputation and sensing. These initiatives should be practiced across different stages of co-ideation, co-evaluation, co-design, co-test and co-launch. To better engage consumers and other external parties in value co-creation activities, Banks can consider driving the involvement with financial driver; learning driver; hedonic driver; and personal, social and psychological driver. Theoretical Contribution/Originality: This research has sucessfuly show different theoretical framework of value co-creation strategy to be implemented in Digital Banking industry, especially in the micro-business segment and explore what motivates Digital Banking consumers to collaborate in value co-creation. Research limitation/Implications: The scope of this research is limited only to the micro-business segment in Banking and not exploring other segments. This research will also focus on the area of value co-creation only and will not cover other business functional areas such as sales or branding.